Reproduction and growth of the chaparral geophyte, Zigadenus fremontii (Liliaceae), in relation to fire - Tyler, C.; Borchert, M. (Plant Ecology, 2003)
Zigadenus fremontii is often a striking component of the flora following fire in the chaparral. Like other geophytes, it produces large numbers of flowers in the first spring after a burn. Although these plants are most conspicuous in the early postfire environment, the question that remains is, how do they persist in the interval between fires? To address this we investigated differences in the growth and reproduction of Z. fremontii in burned and unburned chaparral. We monitored marked individuals for nine years at three sites: two that were burned in 1990 and one in the same area that was in unburned mature chaparral. We measured leaf area, and production of flowers and fruits. We also conducted seed experiments in the field to determine the rates and timing of germination. We found that reproduction occurs only in the immediate postfire period: flowering and production of fruits and seeds in the first year following fire, and seedling establishment by year 3. There was a cost of reproduction; plants that flowered (in the burn area) had negative growth rates the following year. In contrast, plants in unburned chaparral, which did not flower, had positive growth rates over the same period. Moreover, plants that produced the most flowers had the lowest growth rates. In the unburned chaparral site, plants were not dormant as predicted from previous literature; instead they produced leaves nearly every year. In most years the average leaf area per plant was greater than that in the burned sites. Our results indicate that postfire reproduction depends on growth and carbohydrate storage in the inter-fire period. We also suggest that this species is relatively long-lived for a herbaceous perennial.
Keywords: bulb; California; fire-dependent reproduction; fire-induced flowering; germination; life-history; long-lived; pityopsis-graminifolia; populations; postfire; seedling establishment; soil fertility